Experiences of wearing support garments by people living with a urostomy. (12th December 2019) - Taylor, Claire; Munro, Julie; Goodman, William; Beeken, Rebecca J; Dames, Nicola; Oliphant, Raymond; Watson, Angus JM; Hubbard, Gill
Abstract : Background: support garments are commonly worn by people with a urostomy but there are no published data about their experiences of doing so. Aims: to identify the views of people living with a urostomy on the role of support garments. Methods: a cross-sectional survey of the stoma population's experiences of support garments was conducted in 2018. Recruitment was by social media. The free-text responses provided by a sub-sample of 58 people out of 103 respondents with a urostomy, were analysed. Findings: thematic analysis revealed four themes: physical self-management; psychosocial self-management; lifestyle; and healthcare advice and support. There were mixed feelings about the value of support garments. Many cited a sense of reassurance and confidence and being able to be more sociable and active; others reported discomfort and uncertainty about their value. Conclusion: these findings add new understanding of experiences of support garments and provide novel theoretical insights about life with a urostomy.